Field Evaluation of Raspberry Cultivars in North Dakota - Wenhao Dai; Amber L. Hermanson; Changhyeon Kim; Qi Zhang (HortTechnology)
In North Dakota, USA, harsh winter conditions cause considerable winter injury to many floricane fruiting raspberries. Short growing seasons in North Dakota inevitably result in an incomplete fruit harvest of primocane fruiting raspberries. In this study, the winter hardiness of six floricane fruiting raspberry and five primocane fruiting raspberry cultivars had been evaluated for multiple years since 2016. Results showed that five floricane cultivars (Prelude, Boyne, Killarney, Nova, and Encore) showed less than 20% buds damaged, whereas cultivar Amethyst had 20% to 50% buds damaged in the winter. Severe bud damage was observed in five primocane fruiting cultivars (Polana, Autumn Bliss, BP-1, Heritage, and Joan J) in which Polana had the least winter bud damage with significant variations among years, followed by Heritage, Joan J, and Autumn Bliss, and BP-1. No winter damage was observed of the root system. In addition, the fruit quality, cane height, and yield of the six floricane fruiting cultivars were evaluated. Results showed that ‘Killarney’ fruit was the largest (2.50 g per berry) followed by ‘Nova’ (2.35), ‘Encore’ (2.24), ‘Amethyst’ (2.12), ‘Prelude’ (1.94), and ‘Boyne’ (1.84). No significant differences in total soluble solid (TSS) among cultivars were observed except that the TSS of Prelude was significantly lower than the other five cultivars. The cane height of ‘Killarney’ was the shortest (75 cm), whereas ‘Amethyst’ grew the longest canes (129 cm). Prelude is the earliest ripening floricane cultivar (late June) with a short harvest duration (20 to 25 days). The fruit harvest of ‘Killarney’, ‘Boyne’, and ‘Nova’ started 3 to 5 days after ‘Prelude’ with a longer harvest duration (25 to 30 days). ‘Encore’ and ‘Amethyst’ were harvested from mid-late July to early-mid August. Yield estimation indicated that ‘Killarney’ and ‘Nova’ produced more berries than other cultivars.